A systematic review of maternal TORCH serology as a screen for suspected fetal infection. (11th December 2021) - Fitzpatrick, Danielle; Holmes, Natasha E.; Hui, Lisa
Abstract: Background: The acronym 'TORCH' refers to well‐recognised causes of perinatal infections: toxoplasmosis, rubella, cytomegalovirus (CMV) and herpes simplex virus (HSV). A TORCH serology panel is often used to test for maternal primary infection following detection of ultrasound abnormalities in pregnancy. Aim: This review aims to estimate the diagnostic yield of maternal TORCH serology in pregnancy following fetal ultrasound abnormalities. Materials and Methods: Primary studies published since 2000 that assessed maternal TORCH serology for suspected fetal infection and included information on indications for testing, definition of positive TORCH serology results, and perinatal outcomes were included. Results: Eight studies with a total of 2538 pregnancies were included. The main indications for testing were polyhydramnios, fetal growth restriction and hyperechogenic bowel. There were 26 confirmed cases of congenital CMV, of which 15 had multiple ultrasound abnormalities. There were no cases of congenital toxoplasmosis, rubella or HSV confirmed in any of the eight studies. Conclusions: The clinical utility of TORCH serology for non‐specific ultrasound abnormalities such as isolated fetal growth restriction or isolated polyhydramnios is low. It is time to retire the TORCH acronym and the reflex ordering of 'TORCH' panels, as their continued use obscures, rather than illuminates, appropriate investigation for fetal ultrasound abnormalities. Key points: What is already known about this topic? The TORCH acronym is traditionally used to refer to a group of recognised causes of perinatal infections: toxoplasmosis, rubella, cytomegalovirus and herpes simplex virus. 'O' refers to 'other' and includes parvovirus, syphilis, varicella zoster virus and enterovirus—all of which are included in this review. However, the utility of 'TORCH' panels for maternal serological testing for non‐specific ultrasound indications such as isolated fetal growth restriction is uncertain. The interpretation of maternal serology can be difficult, particularly when performed during third trimester, and serologies are conclusive only if negative. What does this study add? This study confirms that the clinical utility of TORCH serology for non‐specific ultrasound abnormalities is low, with only 31 confirmed congenital infections out of 2538 pregnant women screened. In particular, the diagnostic yield of TORCH serology for isolated fetal growth restriction was extremely low. Congenital CMV was the only confirmed perinatal infection identified, at a similar rate to previously reported background birth prevalences (0.4%). These results support recent Society for Maternal Fetal Medicine recommendations against routine serological testing for all TORCH infections for late onset growth restriction in the absence of specific clinical risk factors for fetal infection.